Epigenome-wide association meta-analysis of DNA methylation with coffee and tea consumption - Irma Karabegović (Nature Portfolio, 2021)
While coffee and tea consumption has been associated with risk of diseases, their mechanisms of action remain elusive. Here the authors present a large EWAS on coffee and tea consumption in cohorts of European and African-American ancestries, finding that coffee consumption is associated with differential DNA methylation levels at multiple CpGs.